2011
DOI: 10.1089/gtmb.2010.0133
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Melting Analysis Is a More Effective Approach for ScreeningTSCGenes Mutations

Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant disorder with a prevalence of 1 in 95,136 in Taiwan. TSC is characterized by hamartomatous lesions in multiple organ systems. Genetic defects in TSC1 and TSC2 genes are the main causes of TSC. A molecular screening protocol using denaturing high-performance liquid chromatography (dHPLC) followed by DNA sequencing is currently performed to locate the genetic lesions in many clinical laboratories. The current screening approach is time consuming and ineff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Of note, this patient had multifocal tumors (paraffin tissue from the other tumor in the same kidney was not available for testing). Four of the seven alterations detected ( TSC2 p.Y130*; TSC2 splice acceptor variant c.976-1G>A between exon 10 and 11; TSC2 p.L361Sfs; TSC1 p.Y761*) have been previously reported in patients with tuberous sclerosis complex and are thought to be pathogenic 7,8,9,10,11,12 , while the other three ( TSC2 p.L243Hfs; TSC2 p.D1677Afs; TSC1 p.L853Cfs) are considered to be likely pathogenic 6,7 .…”
Section: Resultsmentioning
confidence: 85%
“…Of note, this patient had multifocal tumors (paraffin tissue from the other tumor in the same kidney was not available for testing). Four of the seven alterations detected ( TSC2 p.Y130*; TSC2 splice acceptor variant c.976-1G>A between exon 10 and 11; TSC2 p.L361Sfs; TSC1 p.Y761*) have been previously reported in patients with tuberous sclerosis complex and are thought to be pathogenic 7,8,9,10,11,12 , while the other three ( TSC2 p.L243Hfs; TSC2 p.D1677Afs; TSC1 p.L853Cfs) are considered to be likely pathogenic 6,7 .…”
Section: Resultsmentioning
confidence: 85%
“…The sensitivities of HRM and DHPLC were estimated as 95% and 75% and the specificities were assessed as 91% and 98%, respectively. Based on these results, the authors concluded that their HRM protocol can be used for TSC gene mutation screening for clinical applications (32).…”
Section: Discussionmentioning
confidence: 99%